Calmodulin Binding to Death Receptor 5‐mediated Death‐Inducing Signaling Complex in Breast Cancer Cells. Issue 8 (12th April 2017) - Fancy, Romone M.; Kim, Harrison; Zhou, Tong; Zinn, Kurt R.; Buchsbaum, Donald J.; Song, Yuhua
ABSTRACT: Activation of death receptor‐5 (DR5) leads to the formation of death‐inducing signaling complex (DISC) for apoptotic signaling. TRA‐8, a DR5 specific agonistic antibody, has demonstrated significant cytotoxic activity in vitro and in vivo without inducing hepatotoxicity. Calmodulin (CaM) that is overexpressed in breast cancer plays a critical role in regulating DR5‐mediated apoptosis. However, the mechanism of CaM in regulating DR5‐mediated apoptotic signaling remains unknown. In this study, we characterized CaM binding to DR5‐mediated DISC for apoptosis in TRA‐8 sensitive breast cancer cell lines using co‐immunoprecipitation, fluorescence microscopic imaging, caspase signaling analysis, and cell viability assay. Results show that upon DR5 activation, CaM was recruited into DR5‐mediated DISC in a calcium dependent manner. CaM antagonist, trifluoperazine (TFP), inhibited CaM recruitment into the DISC and attenuated DISC formation. DR5 oligomerization is critical for DISC formation for apoptosis. TFP decreased TRA‐8 activated DR5 oligomerization, which was consistent with TFP's effect on DR5‐mediated DISC formation. TFP and Ca 2+ chelator, EGTA, impeded TRA‐8‐activated caspase‐dependent apoptotic signaling, and TFP decreased TRA‐8‐induced cell cytotoxicity. These results demonstrated CaM binding to DR5‐mediated DISC in a calcium dependent manner and may identify CaM as a key regulator of DR5‐mediated DISC formation for apoptosis in breast cancer. J. Cell. Biochem. 118: 2285–2294, 2017. © 2017 Wiley Periodicals, Inc. Abstract : We characterized calmodulin (CaM) binding to death receptor‐5 (DR5)‐mediated death‐inducing signaling complex (DISC) for apoptosis in TRA‐8 sensitive breast cancer cell lines. Results show that upon DR5 activation, CaM was recruited into DR5‐mediated DISC in a calcium‐dependent manner. CaM antagonist, trifluoperazine (TFP), inhibited CaM recruitment into the DISC, attenuated DISC formation, decreased TRA‐8 activated DR5 oligomerization, and impeded TRA‐8‐activated caspase‐dependent apoptotic signaling.